1997
DOI: 10.2307/2446609
|View full text |Cite
|
Sign up to set email alerts
|

The mode of origin of root buds and root sprouts in the clonal tree Sassafras albidum (Lauraceae)

Abstract: The developmental anatomy of root buds and root sprouts was examined in the clonal tree Sassafras albidum. Root samples from 13 clones that varied widely in age and vigor were sectioned and two types of buds were found, "additional" buds and "reparative" buds. Additional buds form during the early growth of uninjured roots and they perennate by growing outwards in concert with the vascular cambium such that bud traces are produced in the secondary xylem. Reparative buds form de novo in response to senescence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 55 publications
2
32
0
3
Order By: Relevance
“…In our study, the spatial distribution pattern of C. sylvestris changed from random to clustered in response to the fire in the area. Some studies have shown that fire events damage plant aerial parts, causing a reduction in the amount of auxin reaching the roots, which in turn stimulates the development of sprouts (Bosela & Ewers 1997, Hoffmann & Moreira 2002, Rodrigues et al 2004. The sprouts from the roots may then lead to a clustered pattern, since the mean distance between a main trunk and its sprouts depends on the energy cost of root production and the presence of spots favorable to their growth (Hutchings 1997).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the spatial distribution pattern of C. sylvestris changed from random to clustered in response to the fire in the area. Some studies have shown that fire events damage plant aerial parts, causing a reduction in the amount of auxin reaching the roots, which in turn stimulates the development of sprouts (Bosela & Ewers 1997, Hoffmann & Moreira 2002, Rodrigues et al 2004. The sprouts from the roots may then lead to a clustered pattern, since the mean distance between a main trunk and its sprouts depends on the energy cost of root production and the presence of spots favorable to their growth (Hutchings 1997).…”
Section: Resultsmentioning
confidence: 99%
“…28, 29), constituem o principal ou único sistema radicular de manutenção e crescimento dos ramos caulinares. Este mecanismo de propagação parece estar associado à perpetuação de espécies formando populações clonais, conforme observado por Bosela & Ewers (1997), em arvores de Sassafras albidum. Hayashi et al (2001) relataram a presença de brotos caulinares aéreos a partir de raízes longas, localizadas paralelamente à superfície do solo, para algumas espécies arbóreas de um remanescente florestal que sofreu vários incêndios.…”
Section: Resultsunclassified
“…The resulting sprouts are termed root sprouts, root suckers, or root shoots (Wittrock 1884), and also sucker shoots (Jenik 1994). The buds they originate from are termed root buds (Bosela and Ewers 1997). In this article the term root sucker is being used for newly formed ramets; their associated horizontal roots are called spacers.…”
Section: Introductionmentioning
confidence: 99%